The Influence of Tourist Attractions, Tourist Motivation, and Direct Marketing on the Decision to Visit the Amazing Farm Depok D'Kandang Tourist Attraction - Insani, Alisya Nur; Pradini, Gagih; Kusumaningrum, Anisa Putri (International Journal of Education, Information Technology, and Others, 2026)
This study investigates how the decision to visit the D'Kandang Amazing Farm in Depok is influenced by tourist attractions, tourist motivation and direct marketing. The aim of this study is to investigate the extent to which tourist attractions, tourist motivation and direct marketing have a significant influence on visitors' decision to visit D'Kandang Amazing Farm. This study involved 100 respondents who visited the D'Kandang Amazing Farm. Data was collected quantitatively using questionnaires and the results were analysed using the Statistical Package for Social Sciences (SPSS version 25). Probability sampling method was used in this study and descriptive analysis and inferential analysis by multiple linear regression were conducted. The results showed that the decision to visit D'Kandang Amazing Farm is positively and relevantly influenced by tourist attractions, tourist motivation and direct marketing simultaneously